Designing Theoretical Program Syllabus of Training Course Level D For 12 – 15-year-old Soccer players’ coaches - Raheem, Mohammed; Muteeb, Fouad (Journal of Physical Education, 2023)
The research aimed at deigning theoretical program syllabus for level D coaches of 12 – 15-year-old soccer players. This syllabus suits the reality of Iraqi coaches on different level; training and psychological sciences as well as other sciences related to designing syllabus for theoretical program. The researchers used the descriptive method on (115) coaches, lecturers in the Asian referees. They designed a questionnaire for theoretical program syllabus. The data was collected and treated using SPSS to conclude a syllabus for the theoretical program of D level coaches of 12 – 15-year-old Iraqi soccer players as well as its suitability for the age of soccer players that the coaches train.